2014
DOI: 10.1038/srep04935
|View full text |Cite
|
Sign up to set email alerts
|

Tal2 expression is induced by all-trans retinoic acid in P19 cells prior to acquisition of neural fate

Abstract: TAL2 is a member of the basic helix-loop-helix family and is essential for the normal development of the mouse brain. However, the function of TAL2 during brain development is unclear. P19 cells are pluripotent mouse embryonal carcinoma cells that adopt neural fates upon exposure to all-trans retinoic acid (atRA) and culture in suspension. We found that the expression of Tal2 gene was induced in P19 cells after addition of atRA in suspension culture. Tal2 expression was detected within 3 h after the induction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Both TMEM38A , highly specific for SkM, and the related TMEM38B , preferentially expressed in SkM but less specific for this tissue, have five exons, but with large differences in intron patterning that are reflected in different distributions of SkM enhancer chromatin at these genes (Figure 5b and d). The upstream neighbor of TMEM38B is the 0.7-kb intron-less TAL2 gene, which encodes an oncogenic TF essential for normal brain development in mice and implicated in osteoclastogenesis [46, 47]. Although TAL2 has not been described as related to SkM, we found that the highest (albeit low) steady-state levels of its RNA among the 53 studied tissues were in SkM (TPM, 0.7) and testis (TPM, 0.9; Table S4b and Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Both TMEM38A , highly specific for SkM, and the related TMEM38B , preferentially expressed in SkM but less specific for this tissue, have five exons, but with large differences in intron patterning that are reflected in different distributions of SkM enhancer chromatin at these genes (Figure 5b and d). The upstream neighbor of TMEM38B is the 0.7-kb intron-less TAL2 gene, which encodes an oncogenic TF essential for normal brain development in mice and implicated in osteoclastogenesis [46, 47]. Although TAL2 has not been described as related to SkM, we found that the highest (albeit low) steady-state levels of its RNA among the 53 studied tissues were in SkM (TPM, 0.7) and testis (TPM, 0.9; Table S4b and Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…3E,F; Voronova et al 2011;Huang et al 2012Huang et al , 2015; Gata3 [Martinez-Monedero et al 2008]). Interestingly, however, the expression of some P19-specific TGs was already affected during the first hours of RA-treatment, among them, the TFs Gbx2 (Bouillet et al 1995;Inoue et al 2012;Nakayama et al 2013), and Tal2, which is essential for midbrain neurogenesis (Achim et al 2013) and contains an intronic RA response element (Kobayashi et al 2014(Kobayashi et al , 2015. We identified two additional RXRA binding sites proximal to Tal2-a constitutive RXRA binding site ∼3 kb downstream from the coding region and a second site upstream of the transcription start site (TSS) (∼5 kb), which is similarly occupied in the absence of ligand but persists only until 6 h after initiating RA treatment (Fig.…”
Section: Ra Induces Both Common and Cell Fatespecific Programs In F9 mentioning
confidence: 99%
“…5) In this study, we focused on the regulatory region involved in the transcription of Tal2. Our data suggest that transcription of Tal2 is mediated by two distal regulatory elements: the TATA-box-like element "TATA(Tal2)" and the RARE-like element "DR5(Tal2)."…”
Section: Resultsmentioning
confidence: 99%
“…5) atRA signaling regulates the transcription of target genes through RARE. Thus, we searched for a RARE motif that might be involved in the transcription of Tal2, and found a putative motif, the RARE-like element "DR5(Tal2)."…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation